Electric-field assisted switching of magnetization in perpendicularly magnetized (Ga, Mn)As films at high temperatures. (30th November 2016) - Wang, Hailong; Ma, Jialin; Yu, Xueze; Yu, Zhifeng; Zhao, Jianhua
Abstract: The electric-field effects on the magnetism in perpendicularly magnetized (Ga, Mn)As films at high temperatures have been investigated. An electric-field as high as 0.6 V nm −1 is applied by utilizing a solid-state dielectric Al2 O3 film as a gate insulator. The coercive field, saturation magnetization and magnetic anisotropy have been clearly changed by the gate electric-field, which are detected via the anomalous Hall effect. In terms of the Curie temperature, a variation of about 3 K is observed as determined by the temperature derivative of the sheet resistance. In addition, electrical switching of the magnetization assisted by a fixed external magnetic field at 120 K is demonstrated, employing the gate-controlled coercive field. The above experimental results have been attributed to the gate voltage modulation of the hole density in (Ga, Mn)As films, since the ferromagnetism in (Ga, Mn)As is carrier-mediated. The limited modulation magnitude of magnetism is found to result from the strong charge screening effect introduced by the high hole concentration up to 1.10  ×  10 21 cm −3, while the variation of the hole density is only about 1.16  ×  10 20 cm −3 .